2007
DOI: 10.1152/ajpregu.00620.2005
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α neutralization ameliorates obstruction-induced renal fibrosis and dysfunction

Abstract: Meldrum KK, Misseri R, Metcalfe P, Dinarello CA, Hile KL, Meldrum DR. TNF-␣ neutralization ameliorates obstruction-induced renal fibrosis and dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 39 publications
(64 reference statements)
4
72
1
2
Order By: Relevance
“…Moreover, TNFa can inhibit VDR expression while enhancing the ability of TGFb1 to stimulate EMT in breast cancer cells, as determined by the induction of a-SMA and the loss of E-cadherin. This is in accord with previous research from our group and others which has identified both the inhibitory effect of TNFa on VDR expression in different cell lines and the synergistic effect of TNFa and TGFb1 on EMT induction (14,27,28).…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, TNFa can inhibit VDR expression while enhancing the ability of TGFb1 to stimulate EMT in breast cancer cells, as determined by the induction of a-SMA and the loss of E-cadherin. This is in accord with previous research from our group and others which has identified both the inhibitory effect of TNFa on VDR expression in different cell lines and the synergistic effect of TNFa and TGFb1 on EMT induction (14,27,28).…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with previous reports linking inflammatory infiltration to cytokine release, ECM imbalance, and fibrosis. 2,47,48 TNF␣ plays an important role in mediating renal fibrosis and dysfunction in response to UUO 31,33 and chemotherapy-induced nephropathy. 49 TNF␣-induced injury is mediated via both its receptors, TNFR1 and TNFR2, with clear evidence for a proapoptotic role in renal tissue.…”
Section: Increased Timp3 Levels In Human Kidney Diseasementioning
confidence: 99%
“…Thus, it is reasonable to speculate that infiltrating mononuclear phagocytes in obstructed kidney play a pivotal role in eliciting tubular apoptosis by stimulating expression of TNF-α and/or TGF-β. TNF-α neutralization also ameliorates obstruction-induced renal fibrosis (26). TGF-β is highly correlated to the fibrogenic process, directly stimulates production of extracellular matrix and myofibroblast transdifferentiation, and plays a central role in renal fibrosis (27).…”
Section: Depleted F4/ 80mentioning
confidence: 99%